Pensamientos Extraordinarios. Sabiduría para la vida diaria. Bruce Lee - Héctor P. Fariña López (Universidad de León, 2012)
John Little. Dojo Ediciones, 2006. 188 páginas. 15x21 cm. I.S.B.N.: 978-84-935400-3-6.